Better Innovation for a Better World - Dahl, Darren W.; Noble, Charles H.; Schreier, Martin; Toubia, Olivier (Journal of Marketing, 2025)
The authors aim to stimulate discussion on how innovation research within marketing can use a better world (BW) perspective to help innovation become a driver of positive change in the world. This “Challenging the Boundaries of Marketing” series article is intended to provide purposeful research opportunities for scholars seeking to bridge innovation research with the BW movement. The authors frame the discussion with four areas of innovation research in marketing that are particularly relevant to BW objectives. They discuss how the innovation process may be disrupted by potentially relinquishing customer centricity and embracing the constraints imposed by BW objectives. They explore how firms should organize for BW innovation, in terms of both who should be involved in the process internally and externally and how the workforce and firm should be structured to support BW innovation. The authors then consider consumer response to innovation from a BW perspective, examining drivers of adoption behavior regarding BW innovations and how these innovations should be marketed; they also explore postadoption behavior and how to help consumers resist adoption in certain contexts. Finally, they discuss how markets for BW innovation may be created and sustained, and how external constituencies (i.e., government, lawmakers, and academic communities) could shape these markets.